Experiences of using the i-PARIHS framework: a co-designed case study of four multi-site implementation projects - S. C. Hunter; B. Kim; A. Mudge; L. Hall; A. Young; P. McRae; A. L. Kitson (BMC, 2020)
Abstract Background The integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) framework is an implementation framework that has been developed and refined over the last 20 years. Its underlying philosophy is that implementing research into healthcare practice is complex, unpredictable and non-linear which therefore requires a flexible and responsive approach to implementation. Facilitation is recognized as the central ingredient of this approach, and i-PARIHS now provides a Facilitation Guide with associated tools. This multiple case study of four implementation projects explored how the i-PARIHS framework has been practically operationalized by diverse implementation project teams. Methods A co-design approach was used to elicit the experiences of four implementation project teams who used the i-PARIHS framework to guide their implementation approach. We conducted the established co-design steps of (i) setting up for success, (ii) gathering the experience, and (iii) understanding the experience. In particular we explored teams' approaches to setting up their projects; why and how they used the i-PARIHS framework and what they learnt from the experience. Results We found both commonalities and differences in the use of i-PARIHS across the four implementation projects: (i) all the projects used the Facilitation Checklist that accompanies i-PARIHS as a starting point, (ii) the projects differed in how facilitation was carried out, (iii) existing tools were adapted for distinct phases: pre-implementation, during implementation, and post-implementation stages; and (iv) project-specific tools were often developed for monitoring implementation activities and fidelity. Conclusions We have provided a detailed overview of how current users of i-PARIHS are operationalising the framework, which existing tools they are using or adapting to use, and where they have needed to develop new tools to best utilise the framework. Importantly, this study highlights the value of existing tools from the published i-PARIHS Facilitation Guide and provides a starting point to further refine and add to these tools within a future Mobilising Implementation of i-PARIHS (or "Mi-PARIHS") suite of resources. Specifically, Mi-PARIHS might include more explicit guidance and/or tools for developing a structured implementation plan and monitoring fidelity to the implementation plan, including recording how strategies are tailored to an evolving context.